Digital Portfolio Assesment: A Self-Reflection Way for Teachers and Special Need Students - Kurniawan, Redite; Khukmi, Khusniatul (Journal of ICSAR, 2023)
Technology and the internet are useful in learning recently. One of them is through digital portfolio assessment as a whole part of learning for special needs students. The purpose of this study is to find out a theory that digital portfolio is not only useful for figure out the progress of achievement of special needs students, but also become a way of self-reflection for teachers and students in learning. The method used in this study was a grounded theory approach with the following steps: 1). Theorization of research by collecting theories on portfolio/digital portfolio assessment as well as self-reflective teachers and students in inclusive school, 2). Collecting data and relevant theoretical samples to the topic, 3). Data analysis to produce a new theory. The results showed that the digital portfolio assessment benefits for increasing the achievement of the development of special needs students as well as self-reflection for teachers and special needs students. As a self-reflection, digital portfolio assessment fulfills the following elements: 1). Increase emotional intelligences, 2). Connecting knowledge and feelings with learning experiences, 3). Emotional engagement with learning experiences.